Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a)\frac{3}{8}+\frac{2}{5}+\frac{5}{8}=\left(\frac{3}{8}+\frac{5}{8}\right)+\frac{2}{5}=1+\frac{2}{5}=\frac{7}{5}\)
\(b)\frac{5}{7}.\frac{2}{3}.\frac{14}{15}=\frac{5.2.14}{7.3.15}=\frac{4}{9}\)
\(c)\frac{3}{8}+\frac{2}{5}.\frac{5}{8}=\frac{3}{8}+\frac{1}{4}=\frac{3}{8}+\frac{2}{8}=\frac{5}{8}\)
\(d)\frac{11}{15}-\left(\frac{2}{3}-\frac{1}{5}\right)=\frac{11}{15}-\frac{7}{15}=\frac{4}{15}\)
~Học tốt~
\(a)\frac{3}{8}+\frac{2}{5}+\frac{5}{8}=\left(\frac{3}{8}+\frac{5}{8}\right)+\frac{2}{5}=1+\frac{2}{5}=\frac{7}{5}\)
\(b)\frac{5}{7}.\frac{2}{3}.\frac{14}{15}=\frac{5.2.14}{7.3.15}=\frac{4}{9}\)
\(c)\frac{3}{8}+\frac{2}{5}.\frac{5}{8}=\frac{3}{8}+\frac{1}{4}=\frac{3}{8}+\frac{2}{8}=\frac{5}{8}\)
\(d)\frac{11}{15}-\left(\frac{2}{3}-\frac{1}{5}\right)=\frac{11}{15}-\frac{7}{15}=\frac{4}{15}\)
~Học tốt~
a) \(\frac{3}{8}+\frac{2}{5}+\frac{5}{8}=\frac{3}{8}+\frac{5}{8}+\frac{2}{5}=\frac{3+5}{8}+\frac{2}{5}\)
\(=1+\frac{2}{5}=\frac{5}{5}+\frac{2}{5}=\frac{7}{5}\)
b) \(\frac{5}{7}\times\frac{2}{3}\times\frac{14}{15}=\frac{5}{7}\times\frac{14}{15}\times\frac{2}{3}=\frac{5\times2\times7}{7\times3\times5}\times\frac{2}{3}\)
\(=\frac{2}{3}\times\frac{2}{3}=\frac{4}{9}\)
c) \(\frac{3}{8}+\frac{2}{5}\times\frac{5}{8}=\frac{3}{8}+\frac{2\times5}{5\times8}=\frac{3}{8}+\frac{2}{8}\)
\(=\frac{5}{8}\)
d) \(\frac{11}{15}-\left(\frac{2}{3}-\frac{1}{5}\right)=\frac{11}{15}-\frac{2}{3}+\frac{1}{5}=\frac{11}{15}-\frac{2\times5}{3\times5}+\frac{3\times1}{3\times5}\)
\(=\frac{11}{15}-\frac{10}{15}+\frac{3}{15}=\frac{11-10+3}{15}=\frac{4}{15}\)
\(\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}:7+\frac{6}{5}\)
\(=\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}\times\frac{1}{7}+\frac{6}{5}\)
\(=\frac{3}{5}\times\left(\frac{6}{7}+\frac{1}{7}\right)+\frac{6}{5}\)
\(=\frac{3}{5}\times1+\frac{6}{5}\)
\(=\frac{3}{5}+\frac{6}{5}=\frac{9}{5}\)
~ Hok tốt ~
\(\frac{29}{12}:\frac{1}{2}-\frac{5}{12}:\frac{1}{2}-\frac{1}{2}\)
\(=\left(\frac{29}{12}-\frac{5}{12}\right):\frac{1}{2}-\frac{1}{2}\)
\(=2:\frac{1}{2}-\frac{1}{2}\)
\(=4-\frac{1}{2}=\frac{7}{2}\)
~ Hok tốt ~
a)\(\frac{3}{5}+\frac{4}{7}=\frac{21}{35}+\frac{20}{35}=\frac{41}{35}\)
b)\(\frac{2}{3}-\frac{3}{9}=\frac{2}{3}-\frac{1}{3}=\frac{1}{3}\)Hoặc \(\frac{2}{3}-\frac{3}{9}=\frac{6}{9}-\frac{3}{9}=\frac{3}{9}=\frac{1}{3}\)
c)\(\frac{2}{5}\)x\(\frac{8}{11}=\frac{16}{55}\)
d)\(\frac{3}{7}:\frac{6}{14}=\frac{3}{7}\)x\(\frac{14}{6}=\)\(\frac{3x7x2}{7x3x2}\)\(=\)\(1\)
e)\(\frac{3}{8}+\frac{6}{15}:\frac{3}{5}=\frac{3}{8}+\frac{6}{15}\)x\(\frac{5}{3}=\frac{3}{8}+\)\(\frac{2}{3}\)\(=\frac{9}{24}+\frac{16}{24}=\frac{25}{24}\)
Giải cực kì đầy đủ
4/5 x 15/11 x 2/9 = 8/33
4/7 x 2/5 + 4/7 x 3/5 = 4/7
( 5/7 + 7/8 ) x 2 = 89/28
2/14 + 3/7 - 3/14 x 2 = 1/7
tk mình nhé, mk nhanh nhất
\(\frac{5}{7}\)x \(\frac{2}{3}\)x \(\frac{14}{15}\)= \(\frac{5x2x14}{7x3x15}\)= \(\frac{5x2x7x2}{7x3x5x3}\)= \(\frac{2}{3x3}\)= \(\frac{2}{9}\)
C) \(\frac{3}{8}\)+ \(\frac{2}{5}\)x \(\frac{2}{5}\)= \(\frac{3}{8}\)+ \(\frac{4}{25}\)= \(\frac{75}{200}\)+ \(\frac{32}{200}\)= \(\frac{107}{200}\)